Curriculum for bariatric endoscopy and endoscopic treatment of the complications of bariatric surgery: European Society of Gastrointestinal Endoscopy (ESGE) Position Statement - Boškoski, Ivo; Pontecorvi, Valerio; Ibrahim, Mostafa; Huberty, Vincent; Maselli, Roberta; Gölder, Stefan K.; Kral, Jan; Samanta, Jayanta; Patai, Árpád V.; Haidry, Rehan; Hollenbach, Marcus; Pérez-Cuadrado-Robles, Enrique; Silva, Marco; Messmann, Helmut; Tham, Tony C.; Bisschops, Raf (Endoscopy, 2023)
Obesity is a chronic, relapsing, degenerative, multifactorial disease that is associated with many co-morbidities. The global increasing burden of obesity has led to calls for an urgent need for additional treatment options. Given the rapid expansion of bariatric endoscopy and bariatric surgery across Europe, the European Society of Gastrointestinal Endoscopy (ESGE) has recognized the need to formalize and enhance training in bariatric endoscopy and the endoscopic treatment of bariatric surgical adverse events. This manuscript represents the outcome of a formal Delphi process resulting in an official Position Statement of the ESGE and provides a framework to develop and maintain skills in bariatric endoscopy and the endoscopic treatment of bariatric surgical adverse events. This curriculum is set out in terms of the prerequisites prior to training, minimum number of procedures, the steps for training and quality of training, and how competence should be defined and evidenced before independent practice.1 ESGE recommends that every endoscopist should have achieved competence in upper gastrointestinal endoscopy before commencing training in bariatric endoscopy and the endoscopic treatment of bariatric surgical adverse events.2 Trainees in bariatric endoscopy and the endoscopic treatment of the complications of bariatric surgery should have basic knowledge of the definition, classification, and social impact of obesity, its pathophysiology, and its related co-morbidities. The recognition and management of gastrointestinal diseases that are more common in patients with obesity, along with participation in multidisciplinary teams where obese patients are evaluated, are mandatory.3 ESGE recommends that competency in bariatric endoscopy and the endoscopic treatment of the complications of bariatric surgery can be learned by attending validated training courses on simulators initially, structured training courses, and then hands-on training in tertiary referral centers.